Concurrent and Time-Lagged Effects of Social Disorganization on Chlamydia Rate Trajectories Among United States Counties and the District of Columbia, 2010–2015. Issue 6 (June 2019) - Sheehan, Diana M.; Gebrezgi, Merhawi T.; Sanchez, Mariana; Li, Tan; Fennie, Kristopher P.; Trepka, Mary Jo
Abstract : Objective: To examine the longitudinal relationship between social disorganization (SD) and genital Chlamydia trachomatis infection. Methods: US county-level data for 2010 to 2015 were used. Reliability and principal component analysis revealed 2 SD factors: socioeconomic deprivation and demographic instability. Growth curve models examined the degree to which SD factors affected chlamydia rates (number of new reported cases per 100, 000 population) at baseline and over time adjusting for population percentage aged 15 to 24 years, male to female ratio for population aged 15 to 24 years, and rural percentage. Regression models explored 1- and 3-year time-lagged effects. Results: Among 2961 counties, the average baseline chlamydia rate was 320.3 with an average increase of 7.7 cases per year. Higher baseline deprivation was associated with higher baseline chlamydia rates ( P < 0.0001) but lower increases over time ( P < 0.0001). Higher demographic instability was associated with lower baseline rates ( P < 0.0001) but higher increases over time ( P < 0.0001). Deprivation was associated with 1- and 3-year lagged rates ( P < 0.0001). Conclusions: On average, chlamydia rates increased across US counties, and more rapidly for counties with the highest demographic instability. Abstract : A study of US counties found chlamydia rates are continuing to increase and more rapidly for counties with the highest demographic instability.Supplemental digital content is available in the text.